The Need for Software Project Monitoring Methodology: An Exploratory Survey at Malaysian Public Sector (International Journal of Innovative Computing, 2014)
Information Communication Technology (ICT) is one of the enabler for the Malaysian transformation programs. Malaysian Public Sector has formed many ICT strategies that in line with Malaysian transformation programs. Under the enrichment of ICT, many software projects are planned and developed for the Malaysian Public Sector. Successful implementations of software projects are addressed as one of the important foundations that support Malaysian transformation programs especially at the Public Sector of Malaysia. Thus, it is important to make sure that these ICT projects are successfully executed. Therefore, monitoring and controlling software projects are the basic discipline to ensure the success of any software projects. The aim of this paper is to investigate the need of software project monitoring methodology for Malaysian Public Sector. In this paper we deliver insights from the practitioner’s perspectives on software projects monitoring at the Malaysian Public Sector through an exploratory survey. The survey findings indicated that there is a need for software projects monitoring methodology at Malaysian Public Sector. This paper is also ranked 17 important factors that contributing to successful software projects at Malaysian Public Sector. The finding from this paper will be extended by proposing a Key Performance Indicators (KPIs) based Software Project Performance Monitoring Methodology for the Malaysian Public Sector. This paper also discuss the preliminary work that being conducted in order to formulate the proposing a Key Performance Indicators (KPIs) based Software Project Performance Monitoring Methodology. Keywords-component; software project monitoring; software projects successful and failure, critical success factors, public sector